Correlation of dental age, skeletal age, and chronological age among children aged 9-14 years: A retrospective study - Vignesh Palanisamy; Arathi Rao; Ramya Shenoy; Suprabha Srikrishna Baranya (Wolters Kluwer Medknow Publications, 2016)
Background: Growth can be one of the most uncertain variations, but understanding the same is very important for diagnosis and treatment planning. Skeletal age and dental age have been used to determine a child's developmental age. Several researchers have evaluated the association between dental and skeletal maturity with chronologic age on different population. The purpose of the present study was to find out whether dental age estimation can be replaced for skeletal age estimation in the Dakshina Kannada population. Methods: A total of 104 samples equally distributed among both genders in the age group of 9-14 years were selected. Skeletal age was estimated using hand-wrist radiographs and Fishman's skeletal maturation index and dental age was measured using Demirjian's method. Results: Spearman's rank-order correlation coefficients were used to measure the association between the skeletal maturity and dental maturity. The mean ages of male and female samples were determined as 11.89 ± 1.867 years and 12.21 ± 1.473 years, respectively. Chronological age was found to be positively correlated to dental age and skeletal age and found to be statistically significant (P < 0.01). The correlation between dental age and skeletal age was also found to be statistically significant with P < 0.001 and correlation coefficient of 0.683 and 0.704 for males and females. Conclusion: The present study showed a strong relation between the developmental ages in mixed dentition population; hence, dental age can be considered as a replacement in the study population.